Politisasi Agama pada Kampanye Pemenangan Eramas dalam Pilkada Sumatera Utara Tahun 2018 - Miftahul Husna Siregar; Muhammad Arif Nasution; Warjio Warjio (Universitas Medan Area, 2022)
This paper aims to find out the process of politicizing religion carried out by the winning team for the Eramas candidate pair in the 2018 North Sumatra election campaign. The problem in this study aims at the purpose of this research is to see the process of politicizing religion and what patterns are contained in the politicization of religion during the 2018 North Sumatra election campaign. This research uses descriptive and qualitative methods, which focus on focusing on actual and reliable phenomena during the research period. The findings of this study are, the process of politicizing religion carried out by the Eramas winning team by approaching various Islamic religious leaders, carrying out major activities such as remembrance akbar in the Benteng Medan field by inviting famous clerics, running a mobile car program to clean mosques, to politicizing religion. in the Eramas Campaign which was proven by the use of the issue of